Open-Label, Dose Escalation Study of the Safety and Pharmacokinetic Profile of Tefibazumab in Healthy Volunteers - Reilley, Sandra (American Society for Microbiology, 2005)
Tefibazumab (Aurexis) is a humanized monoclonal antibody being evaluated as adjunctive therapy for the treatment of Staphylococcus aureus infections. This open-label, dose escalation study evaluated the safety and pharmacokinetics of tefibazumab in 19 healthy volunteers aged 18 to 69 years. Each subject received a single administration of tefibazumab at a dose of 2, 5, 10, or 20 mg/kg of body weight infused over 15 min. Plasma samples for pharmacokinetic assessments were obtained before infusion as well as 1, 6, 12, and 24 h and 3, 4, 7, 21, 28, 42, and 56 days after dosing. Plasma concentrations of tefibazumab were detected 1 h after the end of the infusion, with a mean maximum concentration of drug in serum (C(max)) of 59, 127, 252, and 492 μg/ml following doses of 2, 5, 10, and 20 mg/kg, respectively. The median time to maximum concentration of drug in serum (T(max)) was 1.0 h for each dose. The mean elimination half-life (t(1/2)) was approximately 22 days. The volume of distribution (V) was 4.7, 6.7, 7.2, and 7.2 liters after doses of 2, 5, 10, and 20 mg/kg, respectively. Clearance (CL) was 6.0, 9.2, 10.2, and 9.9 ml/hr, respectively. At the highest dose, plasma levels of tefibazumab were >100 μg/ml for 21 days. On day 56, the mean plasma concentrations were 6.3, 10.0, 16.4, and 30.5 μg/ml for the 2, 5, 10, and 20 mg/kg doses, respectively. Tefibazumab exhibited linear kinetics across doses of 5, 10, and 20 mg/kg. No anti-tefibazumab antibodies were detected after dosing in any subject. There were no serious adverse events, and tefibazumab was well tolerated over the entire dose range.